Evaluation of the cookies formulated with finger millet plant material for antidiabetic property - Amit Semwal; Shilpa Sharma; Sarswati Prakash Bhatt; Mamta Bisht; Rohit Kumar Trivedi; Vikash Jakhmola (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
Cookies are the most popular bakery food consumed worldwide. The development of reduced-sugar soft cookies by using Finger Millet, Syzygium cumini L. (Jamun) and stevia extract was investigated. In addition to it, Buttermilk powder was used as a bulking agent to improve the flavor, color and texture of the cookies along with other ingredients like flour, margarine, salt, sodium bicarbonate, and water. The creamery method of production was used for cookie preparation. Amounts of water, stevia, and buttermilk powder and baking duration for each formulation were determined by preliminary experiments.  Different formulations use different ratios to find out the best composition for cookies on the basis of palatability. After the selection of the best composition, cookies were prepared for the physiochemical, sensory and nutritional analysis. Sensory analysis was evaluated based on organoleptic properties: color, taste, aroma and overall acceptability on the basis of a 9-point hedonic scale. The physiochemical evaluation included total ash value, total water, and alcoholic extraction, and total moisture content. On the basis of nutritional value comparison, it was found that protein content is higher in our formulation than in other marketed products. Due to the high antioxidant potential and phenolic content of the Finger Millet cookie, it can be used as a therapeutic or functional food source for the treatment of overweight, obesity, and diabetes.